Consonant identification in noise using Hilbert-transform temporal fine-structure speech and recovered-envelope speech for listeners with normal and impaired hearinga) - Léger, Agnès C. (J Acoust Soc Am, 2015)
Consonant-identification ability was examined in normal-hearing (NH) and hearing-impaired (HI) listeners in the presence of steady-state and 10-Hz square-wave interrupted speech-shaped noise. The Hilbert transform was used to process speech stimuli (16 consonants in a-C-a syllables) to present envelope cues, temporal fine-structure (TFS) cues, or envelope cues recovered from TFS speech. The performance of the HI listeners was inferior to that of the NH listeners both in terms of lower levels of performance in the baseline condition and in the need for higher signal-to-noise ratio to yield a given level of performance. For NH listeners, scores were higher in interrupted noise than in steady-state noise for all speech types (indicating substantial masking release). For HI listeners, masking release was typically observed for TFS and recovered-envelope speech but not for unprocessed and envelope speech. For both groups of listeners, TFS and recovered-envelope speech yielded similar levels of performance and consonant confusion patterns. The masking release observed for TFS and recovered-envelope speech may be related to level effects associated with the manner in which the TFS processing interacts with the interrupted noise signal, rather than to the contributions of TFS cues per se.